Impaired activation of the supplementary motor area in Parkinson's disease is reversed when akinesia is treated with apomorphine. - Jenkins, I; Fernandez, W; Playford, E; Lees, A; Frackowiak, R; Passingham, R; Brooks, D (1992)
Using positron emission tomography (PET) we previously showed that activation of the putamen, supplementary motor area, and cingulate cortex is impaired in patients with Parkinson's disease (PD) when they are off treatment and perform volitional motor tasks. Evidence suggests that these areas are involved in the generation of internally cued movements in normal subjects. We have now studied the effect of the dopamine agonist apomorphine on cerebral activation when used to treat the akinesia of PD. Regional cerebral blood flow was measured using C15O2 PET in PD patients at rest and when performing paced joystick movements with the right hand in one of four freely chosen directions. All patients used apomorphine regularly, and were studied before treatment, while still "off" but receiving a subcutaneous apomorphine infusion, and when switched "on" with apomorphine. Significant increases in regional cerebral blood flow were determined using statistical parametric mapping. Under resting conditions apomorphine had no effect on focal or global cerebral blood flow. Seven patients with PD performed the motor task adequately in the "off" and "on" states. This group of subjects demonstrated impaired activation of the supplementary motor area and contralateral putamen in the "off" state. Activation of the supplementary motor area significantly improved when the akinesia was reversed with apomorphine. We conclude that the concomitant improvement of supplementary motor area activation and motor function in apomorphine-treated patients with PD provides further evidence for the role of this structure in generating motor programs.